2012
DOI: 10.1111/j.1095-8649.2012.03474.x
|View full text |Cite
|
Sign up to set email alerts
|

A deleterious effect associated with UNH159 is attenuated in twin embryos of an inbred line of blue tilapia Oreochromis aureus

Abstract: Offspring of a highly inbred gynogenetic line of Oreochromis aureus displayed 12-fold increase in twinning rate compared to the outbred population. Asymmetric conjoined twins, which consist of a normal embryo attached to a malformed-atrophic twin, were frequently encountered in both gynogenetic (90·7%) and outbred (38·2%) embryos. The monozygotic origin of these twins was determined using five microsatellite markers. Progeny of heterozygous parents for the microsatellite UNH159 were separated into sub-sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Although spinal deformities observed in cultured fishes might be explained by environmental factors, including nutritional imbalances, hydrodynamic conditions, and water pollution, the large increase in the number of deformed larvae among DHs raised under identical conditions as the control brown trout suggested also a genetic background of the problem. Our results are paralleled with those obtained in inbred stocks of rainbow trout [8], tilapia (Oreochromis aureus) [29], and zebrafish (Danio rerio) [30], where the increase of homozygosity was followed by the increased rate of larvae with vertebral deformities including lordosis, scoliosis, and kyphosis. In contrast, larval spinal deformities in chinook salmon (Oncorhynchus tshawytscha) were found to be a nonadditive genetic effect and rather result from interactions between parental genomes [31].…”
Section: Discussionsupporting
confidence: 86%
“…Although spinal deformities observed in cultured fishes might be explained by environmental factors, including nutritional imbalances, hydrodynamic conditions, and water pollution, the large increase in the number of deformed larvae among DHs raised under identical conditions as the control brown trout suggested also a genetic background of the problem. Our results are paralleled with those obtained in inbred stocks of rainbow trout [8], tilapia (Oreochromis aureus) [29], and zebrafish (Danio rerio) [30], where the increase of homozygosity was followed by the increased rate of larvae with vertebral deformities including lordosis, scoliosis, and kyphosis. In contrast, larval spinal deformities in chinook salmon (Oncorhynchus tshawytscha) were found to be a nonadditive genetic effect and rather result from interactions between parental genomes [31].…”
Section: Discussionsupporting
confidence: 86%
“…The distortion from expected Mendelian segregation in the second group is typical of genes with deleterious alleles that are linked to sex determination as was previously described for tilapia (Shirak et al . , ). The main theory for explaining why those alleles are not selected out of the population is that the deleterious form finds ‘refuge’ through close linkage to the sex‐determining gene in the heterogametic gender, which in rainbow trout is the Y‐locus (sdY).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the heart rate in conjoined Oreochromis mossambicus twins have been successfully studied from day 2 to 8 after hatching [ 15 ]. Several different techniques can be applied to induce twinning in fish eggs, such as elevated water temperature [ 16 , 17 ], hypoxia [ 18 ], irradiation, gynogenetic inbreeding [ 19 ], induction of mutations [ 20 ], and centrifugation (reviewed in [ 1 ]). That we have observed only one pair of conjoined twins that have survived the first feeding period in our research facility during the last 35 years, and that we found 0.4 % eyed eggs with four eyes in a random population of Atlantic salmon, all hatching to become conjoined twins, supports the notion that conjoined fish twins are rare and very seldom survive the transition from yolk sac absorbtion to external feeding.…”
Section: Discussionmentioning
confidence: 99%